Anti-Cancer Properties of Coix Seed Oil against HT-29 Colon Cells through Regulation of the PI3K/AKT Signaling Pathway - Chunlei Ni (MDPI AG, 2021)
This study aims to observe the effects of coix seed oil (CSO) on HT-29 cells and investigate its possible regulation mechanism of the PI3K/Akt signaling pathway. Fatty acid analysis showed that coix seed oil mainly contains oleic acid (50.54%), linoleic acid (33.76%), palmitic acid (11.74%), and stearic acid (2.45%). Fourier transform infrared results found that the fatty acid functional groups present in the oil matched well with the vegetable oil band. The results from CCK-8 assays showed that CSO dose-dependently and time-dependently inhibited the viability of HT-29 cells in vitro. CSO inhibited cell viability, with IC50 values of 5.30 mg/mL for HT-29 obtained after 24 h treatment. Morphological changes were observed by apoptotic body/cell nucleus DNA (Hoechst 33258) staining using inverted and fluorescence microscopy. Moreover, flow cytometry analysis was used to evaluate the cell cycle and cell apoptosis. It showed that CSO induced cell apoptosis and cycle arrest in the G2 phase. Quantitative real-time PCR and Western blotting revealed that CSO induced cell apoptosis by downregulating the PI3K/AKT signaling pathway. Additionally, CSO can cause apoptosis in cancer cells by activating caspase-3, up-regulating Bax, and down-regulating Bcl-2. In conclusion, the results revealed that CSO induced G2 arrest and apoptosis of HT-29 cells by regulating the PI3K/AKT signaling pathway.